Optimalisasi Pelayanan Haji terhadap Jamaah Perempuan - Siti Zulaikha (Multazam : Jurnal Manajemen Haji dan Umrah, 2021)
Abstract: The purpose of this study was to determine the specifications of services for female pilgrims. This type of research is library research with descriptive-analytic nature, where the authors try to explain the situation or existing hypotheses. Sources of data needed in this study are data obtained from official documents, books related to the object of research, research results in the form of reports, theses, theses, dissertations, and laws and regulations regarding Hajj. The results of this study are services for female pilgrims are the same as male pilgrims, namely administrative services, pilgrimage guidance, accommodation, transportation, health services, security and other things needed by pilgrims. So that the pilgrims can perform the pilgrimage safely, comfortably and smoothly in accordance with the teachings of Islam, then the organization of Hajj and Umrah is obliged to provide guidance, service and protection as well as possible to the pilgrims.